Differential roles of interferons in innate responses to mucosal viral infections. Issue 11 (November 2021) - Walker, Forrest C.; Sridhar, Pratyush R.; Baldridge, Megan T.
Abstract : Interferons (IFNs) are among the first vertebrate immune pathways activated upon viral infection and are crucial for control of viral replication and dissemination, especially at mucosal surfaces as key locations for host exposure to pathogens. Inhibition of viral establishment and spread at and from these mucosal sites is paramount for preventing severe disease, while concomitantly limiting putative detrimental effects of inflammation. Here, we compare the roles of type I, II, and III IFNs in regulating three archetypal viruses – norovirus, herpes simplex virus, and severe acute respiratory virus coronavirus 2 (SARS-CoV-2) – which infect distinct mammalian mucosal tissues. Emerging paradigms include highly specific roles for IFNs in limiting local versus systemic infection, synergistic activities, and a spectrum of protective versus detrimental effects of IFNs during the infection response. Highlights: Interferons are crucial regulators of mucosal viral infections in vertebrates, with unique roles influenced by both cytokine and receptor expression in varying cells and tissues. Type I interferons are key for restricting spread of viruses beyond their initial mucosal site of infection, but also may contribute to pathology in human diseases including COVID-19. Type II interferon exerts less well-studied antiviral activities, especially in concert with type I interferons. Type III interferons restrict virus infections within mucosal tissues and may induce less systemic inflammation than type I interferons. Viruses have evolved a plethora of strategies to antagonize interferon signaling. Interferons and/or specific interferon-stimulated genes bear therapeutic promise, though extensive consideration must be given to amelioration of their deleterious effects.